MicroRNA: Potential biomarker and target of therapy in acute lung injury. (November 2020) - Jiang, Z-F; Zhang, L; Shen, J
MicroRNAs (miRNAs) are small noncoding RNAs stretching over 18–22 nucleotides and considered to be modifiers of many respiratory diseases. They are highly evolutionary conserved and have been implicated in several biological processes, including cell proliferation, apoptosis, differentiation, among others. Acute lung injury (ALI) is a fatal disease commonly caused by direct or indirect injury factors and has a high mortality rate in intensive care unit. Changes in expression of several types of miRNAs have been reported in patients with ALI. Some miRNAs suppress cellular injury and accelerate the recovery of ALI by targeting specific molecules and decreasing excessive immune response. For this reason, miRNAs are proposed as potential biomarkers for ALI and as therapeutic targets for this disease. This review summarizes current evidence supporting the role of miRNAs in ALI.